Primary hepatic actinomycosis mimicking a tumor (inflammatory pseudotumor): Case report and literature review - Batırel, Ayşe; Arslan, Ferhat; Hallaç Keser, Sevinç; Küçük, Hasan Fehmi; Yavuzer, Dilek; Karabay, Oğuz; Özer, Serdar (Journal of Microbiology and Infectious Diseases, 2015)
Actinomycosis often manifests with abscesses in the cervicofacial region. Hepatic involvement occurs usually secondary to an intraabdominal infection. "Isolated or primary hepatic actinomycosis (PHA) defines actinomycosis in which the source of infection cannot be demonstrated elsewhere. Herein, we aimed to highlight hepatic actinomycosis in the differential diagnosis of hepatic mass lesions, and also its occurrence even in patients without underlying risk factors. A 24-year-old man, who presented with epigastric and right-upper-quadrant abdominal pain, fever, weight loss, and had a tumor-like mass in the liver was admitted to our hospital. He had no predisposing risk factors or comorbidities. We reviewed all the cases with PHA, who had no predisposing risk factors, in English medical literature from 1993 to 2014. Actinomycotic hepatic pseudotumors should be considered in the differential diagnosis of solitary liver lesions even in patients without any predisposing factors. Multi-disciplinary approach is important in the diagnosis and management.

Aktinomikoz genellikle servikofasiyal bölgede abseler şeklinde ortaya çıkar. Karaciğer tutulumu çoğunlukla batın içi enfeksiyonlara ikincil olarak gelişir. "İzole veya Primer Hepatik Aktinomikoz (PHA)" başka bir enfeksiyon odağının gösterilemediği karaciğer yerleşimli aktinomikozu tanımlar. Burada, hepatik aktinomikozun karaciğerde saptanan kitle lezyonlarının ayırıcı tanısında yer alması gerektiğini ve risk faktörü olmayan hastalarda da gelişebileceğini vurgulamayı amaçladık. Epigastrik hassasiyet, sağ üst kadran ağrısı, ateş, kilo kaybı yakınmalarıyla başvuran 24 yaşında erkek hasta, görüntülemede karaciğerde tümör-benzeri kitle saptanması nedeniyle hastanemize yatırıldı. Hastanın, Aktinomikoz için herhangi bir risk faktörü veya eşlik eden hastalığı yoktu. İngilizce tıp literatüründeki 1993-2014 yılları arasındaki tüm benzer PHA olgularını derledik. Aktinomikotik karaciğer psödotümörleri, hiçbir risk faktörü veya ek hastalığı olmayan hastalarda bile soliter karaciğer lezyonlarının ayırıcı tanısında hatırlanmalıdır. Tanı ve tedavide multidisipliner yaklaşım çok önemlidir.
Tümörü taklit eden primer hepatik aktinomikoz (Inflamatuar Psödotümör): Olgu sunumu ve literatür derlemesi
Keywords: Actinomycosis; Actinomyces SPP; Inflammatory Pseudotumor; Liver; Actinomycosis; Actinomyces SPP; Inflamatuvar Psödotümör; Karaciğer